2014
DOI: 10.1155/2014/506971
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Simultaneous Extraction of Luteolin and Apigenin from Tree Peony Pod and Evaluation of Its Antioxidant Activity

Abstract: An efficient microwave-assisted extraction (MAE) technique was employed in simultaneous extraction of luteolin and apigenin from tree peony pod. The MAE procedure was optimized using response surface methodology (RSM) and compared with other conventional extraction techniques of macerate extraction (ME) and heat reflux extraction (HRE). The optimal conditions of MAE were as follows: employing 70% ethanol volume fraction as solvent, soaking time of 4 h, liquid-solid ratio of 10 (mL/g), microwave irradiation pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
2
17
0
1
Order By: Relevance
“…As mentioned above, ischemiainduced oxidative stress in renal tubules and the inflammatory changes are the major underlying causes for tubular cell apoptosis and subsequent crystal formation/deposition. Our results again demonstrated that Tutukon with its potent ingredients: alkaloids, rosmarinic acid, flavonoids [27] apigenin, luteolin [28], ekvizetonin, saponin [29], and essential oils [32], may be protective enough in the limitation of such alterations causing crystal formation at least in experimental animal models. Treatment of the animals with Tutukon provided a significant protection from calcium oxalate deposition and apoptosis in tubular cells.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As mentioned above, ischemiainduced oxidative stress in renal tubules and the inflammatory changes are the major underlying causes for tubular cell apoptosis and subsequent crystal formation/deposition. Our results again demonstrated that Tutukon with its potent ingredients: alkaloids, rosmarinic acid, flavonoids [27] apigenin, luteolin [28], ekvizetonin, saponin [29], and essential oils [32], may be protective enough in the limitation of such alterations causing crystal formation at least in experimental animal models. Treatment of the animals with Tutukon provided a significant protection from calcium oxalate deposition and apoptosis in tubular cells.…”
Section: Discussionsupporting
confidence: 67%
“…Evaluation of the available data in the literature so far did show that majority of these phytotherapeutic agents have diuretic, anti-inflammatory, antioxidant, vasodilating, and spasmolytic effects [25,26]. The active ingredients responsible for such specific effects have been found to be essential oils, flavonoids, saponins, xanthine derivatives and glycosides [25,[27][28][29]. Among the phytotherapeutic agents applied so far, Phyllanthus niruri has been found to be promising in the prevention of stone formation [25,30] due to its potentially active compounds of genus Phyllanthus, alkaloids, flavonoids, lactones, steroids, terpenoids, lignans, and tannins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MW irradiation power is a significant factor influencing the extraction yield, higher power irradiation enhanced the mixture temperature of the sample, and extraction solvent, increasing the mass transfer rates of substances from the sample (Yao et al, ). The extraction yields of luteolin significantly improved when the irradiation power increased to 230 W, but continuously reduced with the more increment of irradiation power, which is possibly due to oxidative or thermal degradation of luteolin by the excessive irradiation (Wang, Yang, Zu, & Zhao, ). The MW irradiation time also affects the extraction yields, as it was observed that the extraction yield was sharply increased by increasing the irradiation time but after a specific time, no significant variation was found.…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…Linolenic acid exhibits antioxidant function, reduces blood fat and cholesterol levels and prevents diseases of heart, head and blood vessels; however, linolenic acid cannot be synthesised by the body itself. (Wang et al ., ; Picklo & Murphy, ). Because of PSO has so many advantages, we had extracted it in our previous study (Sun et al ., ).…”
Section: Introductionmentioning
confidence: 98%